Dampak Pabrik Aspal pada Kondisi Sosial-Ekonomi Masyarakat di Desa Pana, Kecamatan Alla, Kabupaten Enrekang - Nurfahraini, Zarah; Arfan, Amal; Invanni, Ichsan (LaGeografia, 2019)
This study aims to determine: 1) the socio-economic conditions of the community before the asphalt processing, 2) the socio-economic conditions of the community in the presence of asphalt processing, 3) the presence or absence of the impact of the existence of asphalt processing on the socio-economic conditions in Pana Village, Alla District, Regency Enrekang. This research method uses quantitative descriptive analysis of descriptive statistical data and inferential statistics. The population of this study were 300 people with a sample of 75 that was determined using the Slovin formula with an error rate of 10%. The results showed that the socio-economic conditions of the community prior to the asphalt processing were included in the high category and the socio-economic conditions of the community in the presence of asphalt processing were still in the high category. Based on the results of the SPSS analysis it appears that the value of p (sig. (2-tailed)) is 0.100> 0.05 indicating that the presence of asphalt processing does not have a significant impact on the socio-economic conditions of the community in Pana Hamlet. The data in the field also proves that there are several factors that make the existence of asphalt processing not have a significant impact on the socio-economic conditions of the community, such as: labor recruitment is still small due to the asphalt processing location which is still categorized as small industries. being able to work in that location, the community does not have a contribution in the operation of asphalt processing, the existence of asphalt processing only provides an increase in income for its workers rather than the people who do not work in that location